Cars are ready to fly: urban air mobility and psychological process of sustainable travel mode choices - Kim, Jinkyung Jenny; Radic, Aleksandar; Ariza-Montes, Antonio; Chua, Bee-Lia; Koo, Bonhak; Kim, Seongseop; Han, Heesup (Routledge, 2024)
Objective: This study is designed to predict individuals’ pro-social behavior in their choice of travel modes. Specifically, the consumer adoption process and the norm activation model are incorporated as the overarching theoretical model in consideration of the relative advantages of urban air mobility. Background: Urban air mobility, the next generation urban transport system, is all set to fly. Urban air mobility is a notable disruptive innovation in aviation and mobility system as a sustainable means of transportation. Method: Using a quantitative procedure, we developed the theoretical framework based on the existing theories and examined hypotheses using structural equation modeling and invariance test. Results: The findings indicate that the adoption intention toward urban air mobility is driven by problem recognition, awareness, interest, evaluation, ascribed responsibility, and personal norms. In addition, the relative advantage of urban air mobility moderates the relationships between interest and evaluation, and between ascribed responsibility and personal norms. Conclusion: Based on the empirical evidence, this study discusses the findings and subsequent implications for academia. We also address the opportunities for governmental organizations and industry to maximize the utilization of urban air mobility in order to make a city more convenient, cleaner, faster, greener, and safer.